Measuring Efficiency of English Premier League Football Teams with a Data Envelopment Analysis Approach - Asfour, Antypas (2008)
Professional football clubs are extraordinary businesses since their performance is evaluated both on and off the field of play. This study examines how close to their potential English Premier League Clubs play. Employing a deterministic Data Envelopment Analysis Approach, which has proved particularly useful when production involves multiple inputs and outputs, the efficiency of the 13 clubs that remained in the English Premier League throughout the period from 2001/2 to 2006/7, is measured. The input variables selected are total wage bills for all staff and transfer expenditure. Output is measured by points awarded, total revenues and transfer income.